Blood stream infections in children in the first year after liver transplantation at Wits Donald Gordon Medical Centre, South Africa. (27th January 2020) - Duncan, Mary; DeVoll‐Zabrocki, AnneMarie; Etheredge, Harriet R.; Maher, Heather A.; Bouter, Carolyn; Gaylard, Petra; Loveland, Jerome; Fabian, June; Botha, Jean F.
Abstract: Children who undergo liver transplantation and subsequently develop BSI are at risk for adverse outcomes. Research from high‐income settings contrasts the dearth of information from transplant centers in low‐ and middle‐income countries, such as South Africa. Therefore, this study from Johannesburg aimed to describe the clinical and demographic profile of children undergoing liver transplantation, and determine the incidence and pattern of BSI and associated risk factors for BSI during the first year after liver transplant. Pediatric liver transplants performed from 2005 to 2014 were reviewed. Descriptive analyses summarized donor, recipient, and post‐transplant infection characteristics. Association between BSI and sex, cause of liver failure, age, nutritional status, PELD/MELD score, graft type, biliary complications, and acute rejection was determined by Fisher's exact test; and association with length of stay by Cox proportional hazards regression analysis. Survival estimates were determined by the Kaplan‐Meier method. Sixty‐five children received one transplant and four had repeat transplants, totaling 69 procedures. Twenty‐nine BSI occurred in 19/69 (28%) procedures, mostly due to gram‐negative organisms, namely Klebsiella species . Risk for BSI was independently associated with biliary atresia (44% BSI in BA compared to 17% in non‐BA transplants; P = .014) and post‐operative biliary complications (55% BSI in transplants with biliary complications compared to 15% in those without; P = .0013). One‐year recipient and graft survival was 78% (CI 67%‐86%) and 77% (CI 65%‐85%), respectively. In Johannesburg, incident BSI, mostly from gram‐negative bacteria, were associated with biliary atresia and post‐operative biliary complications in children undergoing liver transplantation.